Investigation of the Compressive Strength of Fly Ash and GGBFS-Based Geopolymer Concretes According to Local Materials and Curing Conditions in Southern Iraq - noor munther (Misan Journal of Engineering Sciences)
Geopolymer concrete is still a new construction material in Iraq and needs tremendous research to get more information about the production techniques. This research showcases the characteristics of geopolymer paste produced by treating low-calcium fly ash (FA) and ground granulated blast-furnace slag (GGBFS) with alkaline solution as activa tor. Using GGBFS and FA is not just for sustainable construction, but also for decreasing CO2 emissions from Portland cement usage. The impact of GGBFS and FA on the resistance to compression of geopolymer samples was assessed. T he solution of alkaline activator utilized consists of sodium hydroxide (NaOH) at concentrations of (8-10) M along with sodium silicate (Na2SiO3) with two types of curing (oven at 60°c and Laboratory curing). A test was conducted to mea sure the compressive strength after seven, twenty-eight and ninety days. For geopolymer concrete made with fly ash an d GGBFS 8M (Laboratory curing), and GGBFS 10M (Laboratory curing and oven at 60°C) the compressive strength was (15.43, 24.20, 43.76 and 43.05) MPa respectively for seven days, (20.15, 27, 52.06 and 46.36) MPa for twenty-eigh t days respectively and (20.9,29,54.19and 47.01) for ninety days respectively.The ratios of compressive strength at 7 da ys to 28 days were approximately 76.57%, 89.62%, 84.05%, and 92.86% for geopolymer concrete made with fly ash a nd GGBFS 8M (Laboratory curing), and GGBFS 10M (Laboratory curing and oven at 60°C) the compressive strength. Based on both practical application and strength points of view its clearly that the geopolymer mixture of GGBFS (10 M) at laboratory curing is the most suitable mixture to be used in southern of Iraq especially at summer season